Tunnel Technique for Anterior Interdental Papillary Reconstruction with Amniotic Membrane and PRF Membrane: A case report - Anurag Satpathy1, Bhagyashree Lenka2, Rinkee Mohanty3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Aesthetics play a crucial role in enhancing the outlook and self-assurance of a person.Loss of interdentalpapilla which occurs in the anterior maxillary region, usually known as the “black triangle” is one of thedemanding missions to take in hand as it requires precise and meticulous handling of tissues in the interdentalarea thereby posing a great challenge inperiodontal plastic surgical procedures. Various non-surgical andsurgical techniques have been recommended with varied success rates for its management. The present casereport presents a tunnel technique for interdental papillary reconstruction procedure using platelet-rich fibrinand amniotic membrane.